Effect of Educational Intervention On Nursing Care in Patients Diagnosed with Thalassemia Major: Educational Intervention on Nursing Care in Thalassemia Patients - Tabussam, Sumaira; Afzal, Muhammad; Sarwar, Hajra; Khan, Sadia (Pakistan Journal of Health Sciences, 2022)
Pakistan have highest burden of thalassemia major patients. These patients have life expectancy of ten years in Pakistan which is very low as compare to other countries. High-quality nursing care and management of thalassemia major Patients is essential. Objectives: To evaluates the understanding of nursing care quality among patients of thalassemia major which frequently have an effect on the patient's mental and physical health harmfully. Methods: Quasi experimental study was conducted in Mayo Hospital Lahore. The study population was those nurses who were working in thalassemia care units. 30 nurses have been taken by using purposive sampling technique. Data was collected by using an adopted tool to assess the nurse’s knowledge and their practices about care of thalassemia major patients. Results: Most of the nurses included in the study had a general nursing diploma 29(76.67%). The average experience of nurses was 6.04±3.57 years, and 97.7% of nurses did not receive any training on thalassemia care. Total post knowledge was 49.37±7.686 and total practices score was 61.13±11.672. These findings revealed that continue educational program for nurses improve these variables. Conclusions: The present study depicted that majority of nurses have not received any training about nursing care of thalassemia major patients. So, teaching program had a good impact on nurse's understanding of thalassemia, as well as their practice.